Pengaruh Struktur Modal, Kebijakan Dividen, Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur - Yasin Ihtiarasari; Ngurah Pandji Mertha Agung Durya (Inovatif: Jurnal Ekonomi, Manajemen, Akuntansi, Bisnis Digital dan Kewirausahaan, 2022)
size affect the dependent variable, namely firm value. Firm value is the result of management's work from several dimensions including Net Cash Flow from Investment Decisions, Growth and Cost of Capital. Firm value is an important concept because firm value is an indicator of how the market values the company as a whole. Company value is an important ratio for the company because it affects the welfare of shareholders. In this study, the object that became the research source was the number of observations of manufacturing companies listed on the IDX for the 2017-2020 period, which were selected based on certain criteria with the sample collection method using the purposive sampling method. The data used is secondary data, namely data obtained from the company's financial statements. The results of this study indicate that firm size has an effect on firm value, while capital structure and dividend policy have no effect on firm value.